Constructing and negotiating social participation in old age: experiences of older adults living in urban environments in the United Kingdom. Issue 6 (23rd June 2021) - Woolrych, Ryan; Sixsmith, Judith; Fisher, Jenny; Makita, Meiko; Lawthom, Rebecca; Murray, Michael
Abstract: The age-friendly cities and communities movement has focused on how to better support older adults to age well within urban environments. Central to 'ageing well' and 'active ageing' agendas is ensuring that older adults can participate in meaningful forms of social participation. The benefits of social participation in old age have been well documented, and research amongst community-dwelling older adults has explored some of the neighbourhood qualities that facilitate or impede such forms of engagement. However, understandings of how older adults construct and negotiate social participation within everyday urban environments have been largely unexplored. To address this gap, we present results from 104 interviews conducted with older adults living in three cities and nine neighbourhoods in the United Kingdom (UK). The findings explore three themes generated from the research: 'constructing meaningful social participation in old age', 'negotiating access to social participation' and 'navigating home and community'. Across these themes, the paper describes how experiences of social participation in old age involve a number of inter-connected physical, psychological and social processes experienced by individuals across a range of environmental settings including the home, outdoor spaces and community facilities. The paper concludes by discussing the implications of the findings for practice, specifically in the delivery of age-friendly communities.